ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENERIMAAN DAN PERILAKU PENGGUNAAN SISTEM INFORMASI (Studi Kasus Penerapan System Application Product pada PT Bumi Muria Jaya Karawang-Jawa Barat) - Victor Hendrik; Wahyu Meiranto (Diponegoro Journal of Accounting, 2016)
This study aimed to examine the effect of the performance expectations, effort expectations, social influence and facilitating condition against the behaviour intention of information system.  And to examine the effect of intervening dependent variable,  behaviour intention of information system against the use behaviour of information system. This study uses a model of the Unified Theory of Acceptance and Use of Technology (UTAUT).            Researchers used data derived from questionnaires given to 35 respondents, who are employees of the Accounting PT. Bumi Muria Jaya Karawang, West Java. The questionnaire used in this study was 35 questionnaire. By using regression analysis techniques, the results showed that there is a positive and significant impact on the effort expectations and the facilitating conditions against behaviour intention of information systems. As well as the behaviour intention of information systems has positive and significant effect on the use behavior of information systems. While the performance expectations and social influence do not affect the behaviour intention of the information system.